Eficacia de dos cepas comerciales de Metarhizium anisopliae en el control de picudo negro (Cosmopolites sordidus) y picudo rayado (Metamasius hemipterus) en condiciones de campo y laboratorio. - Garófalo Mora, Ronaldo Andrés (2020)
The use of entomopathogenic fungi in the control of black weevil (Cosmopolites sordidus) and striped weevil (Metamasius hemipterus) is an alternative that is gaining importance within the integrated pest management. One of the main control agents is Metarhizium anisopliae, which causes high mortality rates. The present study aimed to evaluate the efficacy of two commercial strains of M. anisopliae in the control of black weevil and striped weevil under field and laboratory conditions. The field phase was carried out in the “Oasis 1” farm located in the La Esperanza sector and the laboratory phase was carried out in the Microbiology laboratory of the “La María” Campus belonging to the UTEQ. For the field and laboratory experiments, two commercial strains were used: Cepa 1, originating from the Quevedo canton and Cepa 2, originating from the La Concordia canton in liquid formulation. The highest mortality percentage for black weevil and striped weevil occurred when using Strain 2 with values of 32.33% and 51.83% respectively. Under laboratory conditions, Strain 2 reached higher mortality values with 64% and 88% for each of the species. The percentage of efficacy in the field was 30.50% for black weevil and 28.17% for striped weevil. The mean lethal time (TL50) for black weevil and striped weevil inoculated with Strain 2 in the laboratory was 20 days and 9 days respectively. Three species of weevils were found: C. sordidus, M. hemipterus and Polytus mellerborgii at the rate of 297, 680 and 119 specimens for each species.